Customer Retention Challenges in SMEs: A Case Study of Veterinary and Agricultural Pharmacies in Morogoro Municipality - Nedumpilli, Pramodkumar (Journal of Global Economy, Business and Finance, 2025)
The purpose of this study was to examine the challenges on retention of customers in agricultural veterinary in small and medium pharmacies, a case of veterinary and agricultural pharmacies in Morogoro Municipality. The target population of this study was 227 respondents. A sample size of 80 respondents that include 70 small and medium enterprises and 10 customers was used. Simple random sampling techniques and convenience sampling techniques were used in selection of respondents. Data were collected by using questionnaire, interviews and documentary reviews. Quantitative data were analyzed by using descriptive statistics while qualitative data were analyzed by using content analysis. Findings identified the following causes for the lack of customer retention in veterinary and agricultural pharmacies in Morogoro Municipality; poor customer service, the increase of new pharmacies; lack of advertisements and limited convenience. To improve customer retention, recommendations include improving customer service, enhancing convenience, implementing effective advertising, fostering customer loyalty programs, utilizing personalized communication strategies, and encouraging positive word-of-mouth.